Strategi Dakwah dan Pencitraan Diri Jemaat Ahmadiyah - Uwes Fatoni (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2018)
This study describes the strategy of the propaganda of the Ahmadiyah Indonesia (JAI) congregation in facing the resistance of Muslims to create a positive self-image in the community. Using ethnographic studies with da'wah strategy theory, and the dramaturgy theory of this research was carried out in the villages of Tenjowaringin Salawu, and Cipakat Singaparna Tasikmalaya, West Java. The results revealed that the relationship between JAI and the community, especially non-Ahmadiyya Muslims in the villages of Tenjowaringin Salawu and in the Cipakat Village, Tasikmalaya, was quite good. Although there were several explosions caused by provocations from groups outside the community of the two villages, this did not make JAI far from the surrounding community. The propaganda strategy carried out by the Ahmadiyya community was carried out in three activities, namely communication through Rabtah activities, cooperation through charity wikari, and education through the Tarbiyah / School institution. The application of da'wah strategies carried out by JAI was able to shape their positive self-image in the community in accordance with the expectations of the congregation and the management of the Ahmadiyya organization. AbstrakPenelitian ini menggambarkan strategi dakwah jemaat Ahmadiyah Indonesia (JAI) dalam menghadapi resistensi umat Islam untuk menciptakan citra  diri  positif  di  masyarakat. Menggunakan studi etnografi dengan teori strategi dakwah, dan teori dramaturgi penelitian ini dilakukan di desa Tenjowaringin Salawu, dan Cipakat Singaparna Tasikmalaya, Jawa Barat. Hasil penelitian mengungkapkan bahwa hubungan JAI dengan masyarakat khususnya umat Islam non-Ahmadiyah di desa Tenjowaringin Salawu maupun di Desa Cipakat Singaparna Tasikmalaya cukup baik. Meskipun beberapa kali muncul letupan-letupan yang disebabkan oleh provokasi dari kelompok di luar masyarakat dua desa tersebut, namun hal itu tidak menjadikan JAI menjadi jauh dari masyarakat sekitarnya. Strategi dakwah yang dilakukan jemaat Ahmadiyah dilakukan  dalam tiga kegiatan yaitu komunikasi melalui kegiatan Rabtah, kerjasama melalui wikari amal,   dan pendidikan melalui lembaga Tarbiyah/Sekolah. Penerapan Strategi dakwah yang dilakukan oleh JAI mampu membentuk citra diri positif mereka di masyarakat sesuai dengan yang diharapkan oleh jemaah maupun pengurus organisasi Ahmadiyah.